A long noncoding RNA NR_045363 controls cardiomyocyte proliferation and cardiac repair. (February 2019) - Wang, Jue; Chen, Xianda; Shen, Danping; Ge, Donghui; Chen, Jiuling; Pei, Jianqiu; Li, Yandong; Yue, Zhang; Feng, Jie; Chu, Maoping; Nie, Yu
Abstract: Long noncoding RNAs (lncRNAs) play important roles in the regulation of genes involved in cell proliferation. We have previously sought to more globally understand the differences of lncRNA expression between human fetal heart and adult heart to identify some functional lncRNAs which involve in the process of heart repair. We found that a highly conserved long noncoding RNA NR_045363 was mainly expressed in cardiomyocytes and rarely in non-cardiomyocytes. NR_045363 overexpression in 7-day-old mice heart could improve cardiac function and stimulate cardiomyocyte proliferation after myocardial infarction. Furthermore, NR_045363 knockdown inhibited proliferation of primary embryonic cardiomyocytes, while NR_045363 overexpression enhanced DNA synthesis and cytokinesis in neonatal cardiomyocytes in vitro. Mechanistic analysis revealed that NR_045363 promoted cardiomyocyte proliferation through interaction with miR-216a, which regulated the JAK2-STAT3 pathway. Our results showed that NR_045363 is a potent lncRNA modulator essential for cardiomyocyte proliferation. Graphical abstract: Unlabelled Image Highlights: NR_045363 plays a vital role in maintaining cardiomyocyte proliferative capacity shortly after birth. Applying recombinant AAV9:NR_045363 helps repairing injured mice hearts. NR_045363 exerts positive effects on cardiomyocyte proliferation by activating the miR-216a/JAK2-STAT3 pathway.